2018
DOI: 10.3390/ijerph15122882
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3 Gallate Inhibits STAT-1/JAK2/IRF-1/HLA-DR/HLA-B and Reduces CD8 MKG2D Lymphocytes of Alopecia Areata Patients

Abstract: Background: Alopecia areata (AA) is associated with Interferon- γ (IFN-γ) mediated T-lymphocyte dysfunction and increased circulating Interleukine-17 (IL-17) levels. Epigallocatechin-3-gallate (EGCG) specifically inhibits IFN-γ pathways and unlike Janus Kinase 1 and 2 (JAK1/JAK2) inhibitors (tofacitinib, ruxolitinib), EGCG is safer, more cost-effective, and is a topically active agent. Our objective is to test the mode of action of EGCG in vitro and ex vivo using HaCat, Jurkat cell lines, and peripheral blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 88 publications
2
12
0
Order By: Relevance
“…Epigallocatechin-3-gallate has previously been investigated in various inflammatory dermatoses. [19][20][21][22][23]26,28 Green tea consumption has even been proposed as an alternative approach to managing oral LP. 36 The plasma concentration of EGCG detected upon intake of green tea extraction in 350 mL water, 37 however, is far from the concentration needed to achieve antiinflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigallocatechin-3-gallate has previously been investigated in various inflammatory dermatoses. [19][20][21][22][23]26,28 Green tea consumption has even been proposed as an alternative approach to managing oral LP. 36 The plasma concentration of EGCG detected upon intake of green tea extraction in 350 mL water, 37 however, is far from the concentration needed to achieve antiinflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…19 Furthermore, EGCG alleviates psoriasiform [20][21][22] as well as atopic dermatitis-like lesions induced in mice. 23 Particularly, EGCG interferes with different mediators of immune responses activated in ID, including inhibition of nucleic acid sensing pathways 24,25 and Janus Kinase-Signal Transducer And Activator Of Transcription (JAK-STAT) pathways, [26][27][28] whose importance has been underlined in LP 29,30 and other autoimmune skin diseases featuring ID. [31][32][33] In the present study, we investigate the anti-inflammatory effectiveness of EGCG in the human in vitro model established by our working group and thus evaluate it as an innovative topically applicable therapeutic for patients suffering from LP and other autoimmune skin diseases featuring ID.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we have also confirmed that STAT1 protein is one of the potential therapeutic targets of RAS, and this target can be used to screen potential therapeutic compounds. Finally, genistein, daidzein, kaempferol, resveratrol, rosmarinic acid, triptolide, quercetin and (-)-epigallocatechin-3gallate were selceted from the TCMSP databse, and both of them is the STAT-1 inhibitor [48][49][50][51][52]. Interestingly, some of those ingredients, such as rosmarinic acid, quercetin, (-)-Epigallocatechin-3gallate, resveratrol, etc., have already been made into topical formulations for the treatment of oral ulcers, such as quercetin, (-)-Epigallocatechin-3-gallate, resveratrol [53][54][55].…”
Section: Discussmentioning
confidence: 99%
“…Recently, the potential benefits of EGCG for treatment of the autoimmune hair loss condition, AA were reported, where the EGCG appeared to preserve immune privilege in an ex vivo assay, by inhibiting gamma interferon (IFN‐γ) pathways, . Blood samples from female patients with active hair loss and diagnosed AA were compared with age‐matched healthy controls.…”
Section: Phytochemicals For Hair Loss Treatmentmentioning
confidence: 99%
“…Inflammatory T cells and intracellular cytokines (CD4, IFN‐γ, IL‐17) in AA patients' samples were increased in comparison to controls, thus confirming their role in the pathogenesis. Both patient PBLs and HKC (HaCat) were incubated with IFN‐γ, and treated with 40 µM EGCG, which specifically inhibited JAK2 expression, thus blocking the IFN‐γ pathway known to reduce the immune privilege of the HF .…”
Section: Phytochemicals For Hair Loss Treatmentmentioning
confidence: 99%